COMPETENCY AND COMPENSATION ANALYSIS OF WORK PERFORMANCE WITH WORK ENVIRONMENT AS AN INTERVENING VARIABLE IN THE AGENCY FINANCE AND REGIONAL ASSETS OF NORTH SUMATRA PROVINCE - Muhammad Faisal; Elfitra Desy Surya; Mesra B (RADJA PUBLIKA, 2024)
This study aims to analyze the influence of competence and compensation on work performance with the work environment as an intervening variable at the Regional Finance and Asset Agency of North Sumatra Province. The research approach used is quantitative with a survey method by distributing questionnaires to employees as respondents. The research sample was determined using a purposive sampling technique so that the data obtained was in accordance with the research needs of 80 respondents. The data were analyzed using path analysis to measure the direct and indirect effects between variables. The results of the study indicate that competence has a positive and significant effect on work performance, but compensation has a positive but not significant effect on work performance. Competence has a positive and significant effect on the work environment, as well as compensation has a positive and significant effect on work performance. The work environment also has a positive and significant effect on employee work performance. Thus, the work environment is proven to mediate the influence of competence and compensation on employee work performance. The results of this study are expected to be input for management in improving work performance by increasing employee competence, providing appropriate compensation, and creating a supportive work environment.